Language Teaching Research: Meta-Analysis of Reading Interventions for English Learners in STIT Al-Ittihadiyah Labuhanbatu Utara - Siti Ayu Nurhidayati (Yayasan Insan Cipta Medan, 2025)
This meta-analysis investigates the effectiveness of various reading interventions for English learners, with a focus on students at STIT Al-Ittihadiyah Labuhanbatu Utara. The study synthesizes findings from 15 research articles published between 2010 and 2025. The interventions examined include phonics-based instruction, vocabulary development programs, and reading comprehension strategies. The results reveal that phonics-based interventions had the largest effect on reading fluency and accuracy, especially for younger learners. Vocabulary development programs also showed significant improvements in reading comprehension, while reading comprehension strategies were most effective when combined with phonics or vocabulary interventions. The duration of the intervention and the use of digital tools were found to enhance the effectiveness of the programs. This research contributes to the understanding of effective reading interventions for English learners and provides practical recommendations for educators at STIT Al-Ittihadiyah Labuhanbatu Utara.